2002
DOI: 10.1103/physrevb.66.125405
|View full text |Cite
|
Sign up to set email alerts
|

Defects in ultrathin copper nanowires: Atomistic simulations

Abstract: We have performed atomistic simulations for cylindrical multi-shell (CMS)-type Cu nanowires containing defects. Our investigation has revealed some physical properties that have not been detected in previous studies that have considered defect-free nanowires. Since the vacancy formation energy is lowest in the core of a CMS-type nanowire, a vacancy formed in the outer shell of a CMS-type nanowire naturally migrates toward the core. The maximum of the formation energy of an adhered atom on the surface of a CMS-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
0
19
1
Order By: Relevance
“…The authors also considered the recombination mechanisms of vacancies and adatoms in detail. 583 Si NWs with a hexagonal cross section have also been classically 586 In certain crystallographic directions, the two potentials predicted essentially the same behavior of low-energy recoils, while in others there were strong differences. 521 The threshold displacement energy in hexagonal Si NWs with a ͗111͘-oriented axis and with all side facets being ͗112͘ was very recently studied.…”
Section: F Simulation Of Radiation Effects In Nwsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also considered the recombination mechanisms of vacancies and adatoms in detail. 583 Si NWs with a hexagonal cross section have also been classically 586 In certain crystallographic directions, the two potentials predicted essentially the same behavior of low-energy recoils, while in others there were strong differences. 521 The threshold displacement energy in hexagonal Si NWs with a ͗111͘-oriented axis and with all side facets being ͗112͘ was very recently studied.…”
Section: F Simulation Of Radiation Effects In Nwsmentioning
confidence: 99%
“…Defect formation energies in Cu NWs have been studied with classical MD simulations. 583 It was reported that the formation energy of vacancies is the lowest in the middle of the NW. On the other hand, the formation energy of adatoms was reported to decrease with decreasing NW diameter.…”
Section: F Simulation Of Radiation Effects In Nwsmentioning
confidence: 99%
“…[27,28] In the case of Al, Pb, Au, Cu, Rh, and Bi, wires below a certain size have been found to preferentially adopt a multiwalled architecture. The stability of the outer surface determines the stability and properties of the entire structure; this explains the theoretical findings that surface vacancies on such wires would migrate to the core, [25] that melting would first occur in the core, [28] or that the core might be entirely missing, leading to a tube architecture. [29] The outer surface of the wires is predicted to show, in certain ranges of diameter, a helical twist, which would give an unprecedented chirality to the nanowires, [17] similarly to CNTs.…”
mentioning
confidence: 95%
“…[16] Nevertheless, what really inspires a large number of scientists is the possibility of synthesizing, stabilizing, and isolating large numbers of ultrathin nanowires with the unprecedented structures predicted by theory. [17] Most of the work has been performed on metallic nanowires, from elements such as Al, [17] Pb, [17,18] Bi, [19] Si, [20][21][22] Rh, [23] Ag, [24] Cu, [25,26] and Au. [27,28] In the case of Al, Pb, Au, Cu, Rh, and Bi, wires below a certain size have been found to preferentially adopt a multiwalled architecture.…”
mentioning
confidence: 99%
“…Yang et al [28] reported that the stresses in the pre-strained nanowires can be released significantly by the dislocation emission from the cascade core when the strain is greater than 1%. In addition, defect formation energies in Cu nanowires have been studied with the classical MD simulations [29]. It was predicted that the vacancy formation energy is the lowest in the middle of the nanowires and the atom formation energy decreases with the decrease of the nanowires diameter.…”
Section: Introductionmentioning
confidence: 99%